Detection and genetic diversity of subgroup K avian leukosis virus in local chicken breeds in Jiangxi from 2021 to 2023 - Zhang, Fanfan; Li, Haiqin; Lin, Cui; Wei, Yue; Zhang, Weihong; Wu, Yanping; Kang, Zhaofeng (Frontiers in Microbiology, 2024)
Avian leukosis virus subgroup K (ALV-K) is a new subgroup of avian leukosis virus (ALV) that was first identified in Chinese native chickens in recent years. To further understand the molecular epidemiology and evolutionary diversity of ALV-K, this study investigated the molecular epidemiology of 73,664 chicken plasma samples collected from Jiangxi native chicken flocks. The results showed that ALV-J was the most predominant ALV subtype in Jiangxi native chickens, with a high positivity rate of 4.34%. From 2021 to 2023, there was a gradual upward trend in the proportion of positive numbers of ALV-K among ALV-positive samples, and there was a trend of outbreaks. ALV-J and ALV-K were the main co-infection patterns. Genetic evolutionary analysis based on ALV-K gp85 gene showed that the isolated ALV-K in this study were distributed in various branches of the evolutionary tree with genetic diversity. The homology results showed that the amino acid homology of the isolated ALV-K gp85 gene ranged from 33.9% to 88.1% with the reference strains of subtypes A, B, C, D, E, and J, and from 91.9 to 100% with the other ALV-K reference strains.Multiple mutations were present in the ALV-K gp85, and especially significant mutations were found in the highly variable region hr2. The results of ALV-K replication efficiency showed that the replication efficiency of ALV-K was significantly lower than that of ALV-J. These results enriched the genome sequence data of ALV-K in Chinese geoducks, and laid the foundation for further research on the pathogenesis and prevention of ALV-K.